(untitled) (Fiep Bulletin - online, 2012)
The present study compared the performance, in an interceptive task, in function of different motor control strategies (pre-programming, programming and reprogramming). Nine participants (mean, 27 years old) performed the task of pressing a button as soon as an object in movement reached the end of its trajectory in a virtual environment. For pre-programming it was used a constant velocity, for programming three different constant velocities, and for reprogramming repetitions of the constant velocity (probability of 80%) and random velocity (probability of 20%) with increase in the velocity during the half of the track. It were analyzed the constant, absolute, quadratic, and variable error. The results for constant error indicated significant effect (F2,16= 11,75; P= 0,001), in which there was greater error in reprogramming in comparison to pre-programming (P= 0,004) and programming (P= 0,019). It was not found differences for the absolute (F2,16= 1,493; P=0,254), square (F1,9= 0,833; P= 0,400), and variable (F1,8= 0,875; P= 0,381) errors. In preprogramming and programming response directional tendency was anticipated, while in reprogramming the responses were delayed. The advantage in preprogramming was due to specification of the movement control parameters in advance. The reprogramming may be explained by the longer time required in the stages of information processing (response identification, selection, and programming) to readjust the response.